Correction: Sulfur isotope analysis by MC-ICP-MS and application to small medical samples. Issue 4 (18th March 2016) - Albalat, Emmanuelle; Telouk, Philippe; Balter, Vincent; Fujii, Toshiyuki; Bondanese, Victor Paky; Plissonnier, Marie-Laure; Vlaeminck-Guillem, Virginie; Baccheta, Justine; Thiam, Ndiémé; Miossec, Pierre; Zoulim, Fabien; Puisieux, Alain; et al.
Abstract : Correction for 'Sulfur isotope analysis by MC-ICP-MS and application to small medical samples' by Emmanuelle Albalat et al., J. Anal. At. Spectrom., 2016, DOI: ; Web:10.1039/c5ja00489f .